Modeling and simulation of computer networks and systems : methodologies and applications - Obaidat, Mohammad S.; Zarai, Faouzi; Nicopolitidis, Petros (Amsterdam : Elsevier : Morgan Kaufmann, 2015)
Modeling and Simulation of Computer Networks and Systems: Methodologies and Applications introduces you to a broad array of modeling and simulation issues related to computer networks and systems. It focuses on the theories, tools, applications and uses of modeling and simulation in order to effectively optimize networks. It describes methodologies for modeling and simulation of new generations of wireless and mobiles networks and cloud and grid computing systems. Drawing upon years of practical experience and using numerous examples and illustrative applications recognized experts in both academia and industry, discuss: Important and emerging topics in computer networks and systems including but not limited to; modeling, simulation, analysis and security of wireless and mobiles networks especially as they relate to next generation wireless networksMethodologies, strategies and tools, and strategies needed to build computer networks and systems modeling and simulation from the bottom upDifferent network performance metrics including, mobility, congestion, quality of service, security and more... Modeling and Simulation of Computer Networks and Systems is a must have resource for network architects, engineers and researchers who want to gain insight into optimizing network performance through the use of modeling and simulation.
Vendor-supplied metadata.
Includes bibliographical references at the end of each chapters and index.
Keywords: Computer networks; Simulation methods; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Computer networks; Simulation methods; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Electronic books; Electronic books